REVIU HISTORI MODERNISASI PENDIDIKAN ISLAM - Syadidul Kahar (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2019)
The emergence of modernization of Islamic education is inseparable from the awareness of internal renewal as a result of the impact of Ibn Taymiyyah's thoughts. Furthermore, the birth of a new civilization from the West called the Renaissance that gave rise to the central idea of modernization and rational-scientific thought. The condition of Arab countries, such as Egypt and Turkey, is very alarming under the imperialism of European countries, especially France, where Islamic countries are almost entirely controlled by western countries. Finally, at the end of the nineteenth century there was hardly a single Muslim country that had not been touched by Western colonial penetration. Because through Islamic education the formation of Islamic civilization itself. The main purpose of modernization is to build a rational society so that it can face life based on the knowledge and teachings of Islamic values. Based on the perspective of Islamic education, it cannot be denied that the modernization of Islamic education emerged when the Western nations experienced a period of progress. But even so, Islam also experienced a golden age and technological progress. Thus, when the lives of Muslims have experienced the modern period by adopting Western advances, the pattern of modernization experiences differences in building a renewal, both with the concepts of modernization, transformation, reformation, revival, revitalization, actualization, contextualization and westernization. The view of modernization carried out is the knowledge of teachings and science in Islam that can provide solutions to the problems of human life. With a long period of time, modernization in Islamic education does not fully belong to western culture.Keywords:  Review History, Modernization, Islamic Education.